Focal segmental glomerulosclerosis - Saleem, Moin (Henry Stewart Talks, 2016)
The podocyte as the central cell of the glomerular filtration barrier, Podocyte function through cytoskeleton regulation, Pathological altering of cytoskeletal dynamics (genetic defects vs. circulating factors), Restoring normal balance using novel drugs/compounds